36 In-stent restenosis presents as an acute coronary syndrome (ACS) in 40% of cases: not simply a benign clinical entity. (9th June 2011) - Abu-Own, H; Sammut, E; Rathod, K; McGill, L A; Jones, D A; Jain, A; Knight, C; Mathur, A; Wragg, A
Abstract : Background: In-stent restenosis (ISR) following stent implantation may occur in 20% to 40% of the cases according to patient and lesion complexity. Although in the past ISR used to be seen as a "benign" event, more recent studies suggested that a reasonable amount of patients with ISR many develop ACS as the first manifestation of this adverse event. The aim of this study was to determine the different clinical presentations of ISR in a large cohort of consecutive, non-selected patients and compare with native coronary disease. Methods: 14 445 consecutive patients underwent PCI at a single centre (October 2003–May 2010), we identified 922 (6.4%) cases presenting with restenosis after previous PCI. All patients with restenosis presented with new or recurrent symptoms. Demographic and procedural data were collected at the time of intervention (Abstract 36 table 1 ). In-hospital MACE (myocardial infarction, urgent revascularisation, stroke or death) was documented at discharge. All cause mortality data was obtained from the Office of National Statistics via the BCIS/CCAD national audit out to 3.2 years (mean 3.1±1.8 years). Results: Restenosis presented in 60.4% as stable angina, 30.6% as unstable angina/Non-ST elevation MI and 9% with ST-elevation Myocardial Infarction. Cardiogenic shock was reported in 6 patients (0.65%). Women had a higher incidence of unstable angina/non-STEMI compared with men (32.6% vs 29.1%) but a lower incidence of STEMI (5% vs 10.4%). Baseline characteristics are listed in Abstract 36 table 1 . Mortality rate was 0.98% at 30 days, 3.9% at 1 year and 8.7% at 5 years in patients with restenosis. Comparing the restenotic group with those undergoing PCI for de novo coronary artery disease, there were similar ages and incidence of cardiogenic shock but the restenotic group had higher rates of baseline risk factors (diabetes, hypertension, hyerpcholesterolaemia) and higher rates of previous CABG and MI. There was also a higher proportion of South Asians in the restenotic group. See Abstract 36 table 1 . Comparing outcome measures, there were similar rates of inhospital MACE in the 2 groups and over a 5-year follow-up period, there was no difference in all cause mortality. There was no difference in outcome of patients with restenosis vs de novo coronary artery disease regardless of presentation (angina, UA/NSTEMI/STEMI). See Abstract 36 figures 1 and 2 . Conclusions: Clinical in-stent restenosis can frequently present as MI and such patients are more likely to have an aggressive angiographic pattern of restenosis. Drug-eluting stents with improved designs or drug elution systems that further decrease the incidence of ISR are needed.